Transformacja procesu sekularyzacji. Próba kategoryzacji - Iwanicki, Juliusz (Polskie Towarzystwo Religioznawcze, 2012)
Juliusz Iwanicki – TRANSFORMING THE PROCESS OF SECULARIZATION. TRYING CATEGORIZATION The article tries to sort out the theoretical terminology around the category of "secularism". Reference is made here to the four types of secularization: the material, institutional, individual and cultural. The first type of secularism is associated with the loss of wealth in the history of religion by the churches. The second type of secularism is associated with atrophy of the presence of religion in the public space. A third type of secularism - the religious changes within individual units. The fourth and final type of secularization concerns in a cultural secularization. These four types of secularization make possible a comprehensive description of the dynamics of the transformation process of secu-larization. An important argument in the article because it is the claim that secularism is now the transformation of religion rather than its disappearance.